CITIZEN INCLUSION DALAM PRAKTIK GOVERNANCE: Penelusuran Dalam Kebijakan Pendidikan Kota Surakarta - PRIYATNO HARSASTO, DKK, PRIYATNO HARSASTO DKK (Politika: Jurnal Ilmu Politik, 2011)
AbstractInclusion is a requirement for governance to work in the name of policy and public service.Inclusion makes citizen’s voice and aspiration to be included and calculated in public policy. In thisway, inclusion requires the people to be active and the government to be innovative as well as citizenneed-base.This research was conducted in this context. This research tried to elaborate deeper theinvolvement of the citizen in various innovative policies in Surakarta City. The case in point waseducation policy in Surakarta City, especially Bantuan Pendidikan untuk Masyarakat KotaSurakarta/BPMKS (education aid for the people of Surakarta)to find out how far citizen’s inclusionhave been included in the formation of public policy, and what was the stumbling blocs of thisprogram.Using in-depth interview and documentation study, this research found that many sectoralpolicy was still in the hand of technocrats, and citizens’s inclusion was still in the dormant. However,in Surakarta sector policy as well as proggrams, could not be separated from the role of citizen,through Musrenbang, public hearing as well as NGO’s advocacy for the government. In short, thecitizen has indeed owned their inclusion space, but in some cases they have to contend with elitebiases. Moreover, citizen’s inclusion has not been supported by good political communication.Technical and cultural blocks could be said to be the main reasons why inclusion has still been weakin nature.Key words: inclusion, elite-bias, technical and cultural blocks